Halkalı Ziraat Mektebi (1892-1928) - Toruk, İbrahim (My University, 2013)
19. yy.’da Osmanlı Devleti sanayileşen dünyaya ayak uydurabilmek için çabalıyordu. Ekonomisinin temeli tarım olduğu için tarımda sanayileşmeye ayrı bir önem atfediyordu. Bu amaçla yüzyılın ortalarında ilk defa bir ziraat mektebi kurdu. Her ne kadar bu ilk ziraat mektebinin ömrü uzun olmasa da daha sonra ziraat mekteplerinin sayısı ve dereceleri arttı. Halkalı Ziraat Mektebi orta dereceli ziraat okullarından mezun olanların girdiği bir “Ziraat Darülfünunu” konumundaydı. Bu okulun hocaları Avrupa ziraat okullarında okumuşlardı ve aynı zamanda, ülkede mevcut olan geleneksel tarımdan; bilimsel, sanayileşmiş tarıma geçişi sağlamak amacıyla kurulan Ziraat Heyet-i Fenniyesi’nin de üyeleriydiler. Öğrenciler bu okulda tarımsal nesneleri etkileyen iç ve dış faktörleri öğrenip bunların ıslah edilmesi çalışmalarını laboratuvarlarda deneyebiliyorlardı. Bu okuldan mezun olan öğrenciler ülkenin her köşesine ziraat müfettişi veya başka bir zirai bürokrat olarak gönderiliyorlardı. Bir yerde acil bir zirai problem olduğu zaman bu mektepten özel bir heyet hazırlanıp gönderiliyordu. Kısacası Halkalı Ziraat Mektebi tarımda modernleşmenin lokomotifi pozisyonundaydı

In 19th. century, the Ottoman State was trying to keep up with the industrializing world. It was giving great importance to agriculture because the economy was based upon agriculture. For this purpose, it established an agricultural school for the first time in the midst of the century. Although the first agricultural school did not last long, the number of agricultural schools and their degrees increased. The Agricultural School of Halkalı was in the position of a “university of agriculture” where those who graduated from average-degreed agricultural schools could enter. Teachers of these schools studied agriculture in Europe and at the same time they were members of the Scientific Council of Agriculture (Ziraat Heyet-i Fenniyesi) which was established for the purpose of transition from traditional agriculture present in country to scientific and industrialized agriculture. In this school, students could learn the interior and exterior factors that effected agricultural objects and they could experiment the labour of adjustment in laboratories. The students who graduated from this school were being sent to every part of the country as an agricultural inspector or an other agricultural bureaucrat. When there was an urgent agricultural problem somewhere, a special commission was being arranged and sent there from this school. In brief, the Agricultural School of Halkalı was in a position of locomotive in agricultural modernization.
Keywords: Eğitim; Ekonomik Durum; Osmanlı İmparatorluğu, 1299-1918; Tarih; Türkiye